PENGARUH KUALITAS PELAYANAN, HARGA, DAN FITUR TERHADAP KEPUASAAN PELANGGAN GOJEK SAAT PENDEMI COVID-19 DI BANYUWANGI (STUDI KASUS PELANGGAN FITUR GOFOOD) - Alarni, Khalifah Hikmah; Hafidzi, Achmad Hasan; Wibowo, Yohanes Gunawan (Relawan Jurnal Indonesia, 2022)
Study aims to determine and analyze the effect of service quality, price and features on Gojek customer satisfaction during the Covid-19 outbreak in Banyuwagi. The primary data source used in this study is the respondents' answers through questionnaire items. The population of this study is all Gojek customers in Banyuwangi whose number cannot be counted with certainty. Thus the number of samples in this study amounted to 90 respondents. The analytical tool used in this study is multiple linear regression analysis. Many regression test results indicate that service quality has a positive effect on customer satisfaction. This proves that good service quality will increase Gojek customer satisfaction in Banyuwangi. Price has a positive effect on satisfaction. This proves that the right price will increase Gojek customer satisfaction in Banyuwangi. Features have a positive effect on customer satisfaction. This proves that better features will increase Gojek customer satisfaction in Banyuwangi. The results of the partial test (t test) show that service quality, price and features have a significant effect on Gojek customer satisfaction.